PERAN MAHASISWA ASISTENSI MENGAJAR PROGRAM MERDEKA BELAJAR KAMPUS MERDEKA - Pawe, Maria Serlina; Oka, Elisabeth; Lidi, Maria Waldetrudis; Walo, Sesarius (Mitra Mahajana: Jurnal Pengabdian Masyarakat, 2025)
The Teaching Assistance Program is part of the Independent Learning and Independent Campus (MBKM) policy, designed to provide students with opportunities to develop themselves outside the campus through teaching experience in secondary education institutions under the guidance of field supervisors. This study examines the implementation of Teaching Assistance by students from the University of Flores at Tri Dhrama Ende Private Middle School using observation methods, where students directly observe learning activities and the school environment. During the program, students play an active role in various academic and non-academic aspects, including teaching, developing learning materials, assisting with school administration, and participating in both formal and informal activities. The results of this program indicate that the Teaching Assistance program runs well and provides benefits to both students and the school in improving the quality of learning.